Thiazolidinone motif in anticancer drug discovery. Experience of DH LNMU medicinal chemistry scientific group - Lesyk, R. B.; Zimenkovsky, B. S.; Kaminskyy, D. V.; Kryshchyshyn, A. P.; Havryluk, R. B. LD. Ya.; Atamanyuk, D. V.; Subtel’na, I. Yu.; Khyluk, D. V. (Вiopolymers and Cell, 2011)
The aim was analysis of 4-thiazolidinones and related heterocyclic systems anticancer activity data and formation of some rational design directions of potential anticancer agents. Synthetic research carried out in
Danylo Halytsky Lviv National Medical University (DH LNMU) allowed us to propose a whole number of
new molecular design directions of biological active 4-thiazolidinones and related heterocyclic systems, as
well as obtain directed library that numbers over 5000 of novel compounds. At the present time in vitro anticancer activity screening was carried out for more than 1000 compounds (US NCI protocol (Developmental
Therapeutic Program), among them 167 compounds showed high antitumor activity level. For the purpose
of optimization and rational design of highly active molecules with optimal «drug-like» characteristics and
discovering of possible mechanism of action SAR, QSAR analysis and molecular docking were carried out.
The ultimate aim of the project is creating of innovative synthetic drug with special mechanism of action and
sufficient pharmacological and toxicological features. Some aspects of structure–activity relationships
were determined and structure design directions were proposed. The series of active compounds with high
anticancer activity and/or selectivity levels were selected.
Key words: synthesis, 4-thia(imida)zolidinones, thiopyrano[2,3-d]thiazoles, anticancer activity, (Q)SAR. Метою роботи був аналіз результатів дослідження протипухлинної активності 4-азолідонів і споріднених гетероциклічних
сполук та формування деяких напрямків раціонального дизайну
потенційних протипухлинних агентів. Синтетичні дослідження, проведені у ЛНМУ імені Данила Галицького, дозволили запропонувати низку нових спрямувань молекулярного дизайну
біологічно активних 4-тіазолідинонів та споріднених гетероциклічних систем, а також одержати сфокусовану бібліотеку, яка нараховує понад 5000 нових сполук. На цей час здійснено
in vitro скринінг протипухлинної активності понад 1000 сполук
(US NCI протокол Developmental Therapeutic Program), з-поміж яких 167 ідентифіковано як такі, що мають високу протиракову активність. Для оптимізації і раціонального дизайну
високоактивних молекул з оптимальними «лікоподібними» характеристиками та визначення можливого механізму біологічної дії проведено SAR- і QSAR-аналіз і молекулярний докінг.
Кінцевою метою проекту є створення інноваційного синтетичного лікарського препарату з оригінальним механізмом дії
та достатнім фармакологічним і токсикологічним профілем.
Ключові слова: синтез, 4-тіа(іміда)золідинони, тіопірано[2,
3-d]тіазоли, протипухлинна активність, (Q)SAR. Цель работы состояла в анализе результатов исследования
противоопухолевой активности 4-азолидонов и родственных
гетероциклических систем и формировании некоторых направлений рационального дизайна потенциалных противоопухолевых агентов. Синтетические исследования, проведенные в
ЛНМУ имени Данила Галицкого, позволили предложить ряд новых направлений молекулярного дизайна биологически активных 4-тиазолидинонов и родственных гетероциклических систем, а также получить сфокусированную библиотеку, насчитывающую более 5000 новых соединений. На данный момент
осуществлен in vitro скрининг противоопухолевой активности
(US NCI протокол Developmental Therapeutic Program) более
1000 соединений, позволивший идентифицировать 167 соединений с высоким противораковым эффектом. Для оптимизации и рационального дизайна высокоактивных молекул с оптимальными «drug-like» характеристиками и установления вероятного механизма биологического действия проведен SAR- и
QSAR-анализ и молекулярный докинг. Конечная цель проекта –
создание инновацинного синтетического лекарственного
сресдтва с оригинальным механизмом действия, достаточным фармакологическим и токсикологическим профилем.
Ключевые слова: синтез, 4-тиа(имида)золидиноны, тиопирано[2,3-d]тиазолы, противоопухолевая активность, (Q)SAR.